Isthmus characteristics in operated congenital heart disease with atrial tachycardias. (19th May 2022) - Tampakis, K; Capellino, S; Combes, N
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Patients with surgically repaired congenital heart disease (RCHD) present a high prevalence of atrial tachycardias (ATs). Although typical circuits dependent on the cavotricuspid isthmus (CTI-AFL) are the most frequent, intra-atrial re-entrant tachycardias (IART) are also common and a significant cause of recurrence. Purpose: The aim of this observational study was to describe the characteristics of incisional isthmuses identified with ultrahigh‐density electroanatomical mapping in patients with RCHD and to investigate their clinical significance. Methods: The present investigation ambispectively examined 23 patients with RCHD. Mapping of index, induced and recurrent ATs was performed using a multipolar basket catheter and an ultra-high density mapping system. The conduction velocities (CV) and isthmus widths were calculated on isochronal and activation maps (Figure 1). Results: Overall, 33 ATs in 23 patients were mapped in their entirety. 8 patients had no IART as index AT and no other zones of slow conduction. In the remaining 15 patients, 22 ATs were mapped (9 CTI-AFL/13 IART) and 27 zones of slow conduction were identified. All identified critical and/or potential incisional isthmuses had a CV≤0.625 m/sec. By trichotomizing the predictor of CV, all isthmuses (9/9) of the middle third (CV 0.075-0.133 m/sec) were critical for an IART (either index or induced) and they were significantly more frequently associated with an IART (100%) compared with the isthmuses of the upper (44.4%) and lower third (66.7%) (p=0.034). Width of critical isthmuses was significantly narrower compared to width of non-critical isthmuses (10.1±3.1 mm versus 16.3±7.3 mm, p=0.049). Among 9 induced/recurrent IARTs, critical incisional isthmus was visible at the activation map of the index AT in 6 patients (66.7%) and concealed (presented as line of block and/or collision of the wavefronts) in the remaining (33.3%). Index ATs with concealed isthmuses were significantly slower from index ATs without (U=6, p=0.047). During index ATs with cycle length <270 msec all critical isthmuses were visible (sensitivity 100%) (AUC=0.860, p=0.050). Conclusions: The majority of isthmuses related to IARTs can be identified using ultrahigh‐density activation mapping in patients with RCHD. A proportion can be overlooked due to functional block, especially during a slow index AT. CV and width of incisional isthmuses can be easily measured using novel mapping tools. Mid-range slow CV and narrow isthmus width may be predisposing factors of IART. Whether these features should promote ablation irrespective of stimulation protocol for AT induction needs further investigation. Figure 1. Isthmus CV calculation using isochronal activation mapping. Figure 2. An incisional isthmus, critical for an induced IART, was identified during a typical flutter. This isthmus had a narrow width (9.0 mm) and a mid-range slow CV (0.11 m/sec), features that may be predisposing factors for IARTs.